Optimization of the drilling campaign in reducing drilling cost in Block A Asset - Ibnu Hafizh; Hasan Yudie Sastra; Irwansyah Irwansyah (Politeknik Negeri Lhokseumawe, 2022)
Drilling requires large costs with a very high risk of work, therefore good and careful planning is needed before it is carried out to obtain effective and efficient results by considering two aspects i.e. engineering and economics. Unstable conditions at the drilling site pose a high risk from the investor's point of view in terms of the total drilling costs that will be incurred in the area. The Platform drilling campaign implemented in Alur Siwah Phase 1 project is part of a project to increase gas recovery so that meets the gas raw materials demand in Aceh and the campaign is conducted using directional drilling technique. A descriptive method was used in the study and the data was gathered from the drilling activity reports during planning to post-drilling. Optimization using a drilling campaign during the drilling for the three wells in Alur Siwah Fase 1 resulted in a drilling cost savings of 26% and also saved execution time about 37 days from planning time